Faulty fetal packing. (10th March 2011) - Flannigan, Christopher; O'Neill, Conor
Abstract : A male infant was born by emergency caesarean section at 34 +4 weeks for failed induction of labour. Shortly after birth a depression about the same size as the baby's fist was noted over the right parietal region. After careful consideration of the perinatal history and examination findings, the baby was diagnosed with faulty fetal packing. At 3-month follow–up, the defect had completely corrected without intervention.